Landslide Dynamics and Determination Critical Condition Using of Resistivity Method in Desa Negeri Lima Ambon - Matheus Souisa; Lilik Hendrajaya; Gunawan Handayani (Institut Teknologi Bandung, 2015)
Ambon Island is a volcanic island arc and included in the territory of the archipelago of small islands are associated with subduction zones that have a high degree of vulnerability to natural disasters, such as erosion and landslides on a particular slope conditions. This study aims to determine the dynamics of avalanches below the surface in the area of the landslide and determine the position of the gelincirnya. The study area in the mountains of Ulak Hatu Negeri Lima Ambon. Research using geoelectric of resistivity with Wenner-Schlumberger configuration. Geoelectric interpretation results correlated with the drill data to obtain landslide field located at a depth of approximately 5 m - 30 m and lithology dominated by low resistivity values with the structure of a layer of clay mixed with layers of weathered rock and clay layer with water saturated. Both of these layers contact each other and form the slope of the ground, causing the potential for critical slip thereon and allows the subsequent landslides. Critical location landslide direction of the obliquity of the avalanche that is, toward the cliff and the geometry of the type of debris avalanches of rocks and debris flow. Estimation of landslides occur in addition to the local geological conditions, but strongly influenced by rainfall reached 335.0 mm, earthquakes and coupled with a slope of 119.0%.